Physicochemical Properties of Edible Chitosan/Hydroxypropyl Methylcellulose/Lysozyme Films Incorporated with Acidic Electrolyzed Water - Ewa Brychcy; Dominika Kulig; Anna Zimoch-Korzycka; Krzysztof Marycz; Andrzej Jarmoluk (International Journal of Polymer Science)
The treatment with acidic electrolyzed water (AEW) is a promising disinfection method due to its effectiveness in reducing microbial population. The aim of the study was to evaluate physicochemical properties of chitosan/HPMC films incorporated with lysozyme and acidic electrolyzed water. In the composite films, decreasing film solubility and increasing concentration of sodium chloride solution and prolongation of electrolysis time were observed. Electrolysis process with sodium chloride induces spongy network of film structure. The use of AEW has not changed chemical composition of films which was proved by 1H NMR, MALDI-TOF, and FT-IR spectroscopy. The research confirmed that electrolysis significantly improved thermomechanical properties of the examined films. The contact angle values of the films were quite similar and ranged between 56° and 73°. The increase of salt concentration used in the electrolysis process had an impact on increasing flexibility of samples. Application of electrolyzed water in commonly used food processing systems is possible. Fusion of AEW and biopolymers may provide better integration with coated food product and multidirectional protecting effect.